Shear Fracture Behaviour of Bonded Joints by Application of the Direct Integration Method - R. L. Fernandes; R. D. S. G. Campilho (Research and Developments in Engineering Research Vol. 4, 2023)
The shear fracture toughness (Gsc) and CZM laws of bonded joints were investigated in this study. This was accomplished using the End-Notched Flexure (ENF) test geometry. Design can be geared toward lighter constructions using adhesive bonding, not only because of the immediate weight saving advantages of the connection over fastened or welded joints, but also because of the flexibility to link diverse materials. Cohesive Zone Models (CZM) are a strong design tool, but they require the CZM laws of the adhesive bond in tension and shear as input. The experimental effort involved characterizing the bond’s shear fracture using conventional and J-integral approaches. Furthermore, the precise geometry of the cohesive law was established using the J-integral technique. Numerical Finite Element (FE) simulations in Abaqus® were performed to assess the correctness of the generated CZM laws in predicting the experimental behavior of the ENF tests, and the findings were positive. The CZM laws of the tested adhesive revealed a good agreement between specimens. As a result of this work, fracture information in shear for the chosen adhesive is provided, enabling the subsequent strength prediction of bonded joints.